FORMULASI TABLET PARACETAMOL SECARA KEMPA LANGSUNG DENGAN MENGGUNAKAN VARIASI KONSENTRASI AMILUM UBI JALAR (IPOMEA BATATAS LAMK.) SEBAGAI PENGHANCUR - Ani, Nur (Fakultas Farmasi UMI, 2016)
It has been conducted a research about paracetamol tablet formula with kempa technique directly using various concentration of parsnip creeps amylum (Ipomea batatas Lamk.) as dissolver. The result observation shows that all tablet qualifies to test tablet physical character of that. Cover wight uniformity, size uniformity, crispness, and violence, flohat are indicated accord with in Indonesian Pharmacopoeia. Based on analysis of variance quiz f that there is no significant formula among uniformity, size uniformity, crispness and violence. All formula qualifies to test at dissolution.